The concentration of income at the top in Brazil, 2006-2014 - Pedro Herculano Guimar\~aes Ferreira de Souza; Marcelo Medeiros (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
Extreme inequality in Brazil is self-evident. The historian José Murilo de Carvalho emblematically chose to end his book on the history of citizenship in Brazil with the severe diagnosis that 'inequality is the slavery of today, the new cancer that hinders the constitution of a democratic society' (Carvalho 2001, 229). Normative prescriptions aside, not even historical opponents of redistributive policies, such as Mário Henrique Simonsen, failed to recognise - even if reluctantly - income inequality as 'undesirably high', and as a source of 'pained conscience' (Simonsen 1972, 57; 59). [...]
Keywords: 330; concentration; income; top; Brazil; 2006; 2014